2012
DOI: 10.1002/tesq.51
|View full text |Cite
|
Sign up to set email alerts
|

Desire in Translation: White Masculinity and TESOL

Abstract: This article reports on a study of Western male English language teachers and considers the ways in which their identities were shaped in relation to discourses of masculinity and heterosexuality. The article first argues that masculinity and heterosexuality have remained unmarked categories in research on TESOL teacher identities. It then draws on interview data with 11 White Australian men and considers the discourses of gender and sexuality in their accounts of English language teaching in Japanese commerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 32 publications
0
30
0
Order By: Relevance
“…Observations such as those articulated in this section, and in other accounts of white Western men in Japan (Appleby 2013a(Appleby , 2013bHicks 2013), have led Yoko Kobayashi (2014) to suggest that white male native speakers of English may not only be benefiting from 'male-friendly hiring practices' (222), but also be 'tapping into a vein of masculinity in east Asia, which has long marginalized local women' and been denounced in the West as 'backward' and 'sexist' (220).…”
Section: Rationalising the Predominance Of White Western Men Among Fomentioning
confidence: 92%
See 1 more Smart Citation
“…Observations such as those articulated in this section, and in other accounts of white Western men in Japan (Appleby 2013a(Appleby , 2013bHicks 2013), have led Yoko Kobayashi (2014) to suggest that white male native speakers of English may not only be benefiting from 'male-friendly hiring practices' (222), but also be 'tapping into a vein of masculinity in east Asia, which has long marginalized local women' and been denounced in the West as 'backward' and 'sexist' (220).…”
Section: Rationalising the Predominance Of White Western Men Among Fomentioning
confidence: 92%
“…The context of this study This paper arises from a larger research project conducted over a period of five years (2009)(2010)(2011)(2012)(2013) that focused on the effects of gender on the experiences of men and women from Anglophone countries working as English language teachers in Japan (Appleby 2013a(Appleby , 2013b(Appleby , 2014. During that time, I travelled from Australia (my home country) to Japan on four occasions for ethnographic field work, visiting educational institutions and conducting interviews with teachers.…”
Section: Introductionmentioning
confidence: 99%
“…English, as advertised for language schools and presented in textbooks, ‘emerges as a powerful tool to construct a gendered identity and to gain access to the romanticized West’ (Piller & Takahashi, 2006, p. 69). As Motha and Lin (2014, p. 332) contend ‘at the center of every English language learning moment lies desire: desire for the language; for the identities represented by particular accents and varieties of English; for capital, power, and images that are associated with English; for what is believed to lie beyond the doors that English unlocks.’ Takahashi (2013, p. 144) explains Japanese women's desire for English, as ‘constructed at the intersection between the macro‐discourses of the West and foreign men and ideologies of Japanese women's life‐courses in terms of education, occupation, and heterosexuality.’ Focusing on the ways in which these discourses of desire implicate White Western men, Appleby (2013, p. 144) shows how ‘an embodied hegemonic masculinity’ is constructed in the Japanese ELT industry, producing as a commodity ‘an extroverted and eroticised White Western ideal for male teachers.’ Any understanding of the motivations to learn English, therefore, has to deal with relations of power not only in economic and educational terms but also as they are tied to questions of desire, gender, sexuality, and the marketing of English and English language teachers as products. The political economy of English and the possibility of cheap but authentic English are also therefore tied to very real material conditions of sexuality.…”
Section: Governmentality Gender and Scripts Of Servitudementioning
confidence: 99%
“…For example, the plight of struggling immigrant students cannot be attributed solely to the identity inscription of nationality or ethnicity, but must be examined with respect to other categories such as class, gender, and religion. In a study which crosses ethnic, gender, and sexuality divides, Appleby (2012) found, for example, that White Australian men teaching in Japanese language schools struggled to negotiate a particularly complex contact zone, which may have limited their professional and pedagogical aspirations. Also in Japan, Kamada's (2010) study of the hybrid identities of adolescent girls who were 'half' Japanese was focused on issues of both ethnicity and gender, and illustrates how these young women struggled to negotiate desirable identities when confronted by marginalizing discourses.…”
Section: Intersectionalitymentioning
confidence: 99%